PENGONTROLAN SISTEM DIGITAL PADA LABORATORIUM ELEKTRONIKA BERBASIS PEMROGRAMAN DELPHI DENGAN MIKROKONTROLLER - Aris Taufiq (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2009)
To mitigate the risk of fire, we proposed the system wich combine Delphi7 programming language, Microcontroller PIC 16F877 and fire sensor. This system need a computer operator for turning the computer system on or off. If the accident happen, the system will send the message to operator by using the handphone. Although this is just a simulation system, we can build this system for real application because of good experiment result.